2018
DOI: 10.1111/jphs.12238
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative exploration of pharmacist care for herbal and dietary supplement users in Thai community pharmacies

Abstract: Objectives Herbal and dietary supplements (HDS) can cause adverse effects or interact with diseases and medications. Community pharmacists have a role in ensuring the safe use of HDS, but they have been reported to not being proactive in providing pharmacist care (PCare) for HDS users. The reasons for this warranted investigation. The study aimed to explore pharmacists’ understanding of PCare for HDS users, and to investigate the underlying beliefs or factors influencing its provision by community pharmacists,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The survey instrument was developed based on an extensive literature review. Research articles discussing the reasons for consultation with pharmacists around HDS use [ 40 , 41 , 44 , 45 , 46 , 47 ], pharmacist- or HCP-patient communication and relationship [ 48 , 49 ], and complementary medicine disclosure to HCPs [ 50 , 51 , 52 ] were used. Based on the literature review, the consultation and non-consultation with CPs about HDSs can be influenced by the consumers’ perceptions of the consultative roles of CPs with respect to HDSs, facilitators (e.g., having a good relationship with CPs, having adequate time to consult CPs, willingness of CPs to spend time providing consultation, etc.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The survey instrument was developed based on an extensive literature review. Research articles discussing the reasons for consultation with pharmacists around HDS use [ 40 , 41 , 44 , 45 , 46 , 47 ], pharmacist- or HCP-patient communication and relationship [ 48 , 49 ], and complementary medicine disclosure to HCPs [ 50 , 51 , 52 ] were used. Based on the literature review, the consultation and non-consultation with CPs about HDSs can be influenced by the consumers’ perceptions of the consultative roles of CPs with respect to HDSs, facilitators (e.g., having a good relationship with CPs, having adequate time to consult CPs, willingness of CPs to spend time providing consultation, etc.…”
Section: Methodsmentioning
confidence: 99%
“…), and barriers to consult CPs (e.g., feeling uncomfortable discussing HDSs with CPs, not being asked by CPs about HDS use, not having time to consult CPs, etc. ), the health concerns, beliefs of the outcomes of the consultation, and perceived-need of the consultation [ 40 , 41 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacists are expected to encounter HDS frequently at all levels of care due to the accessibility and availability of HDS in retail pharmacies [ 16 , 17 ], and the widespread use of these products among patients. Pharmacists play an important role in educating consumers to ensure appropriate and safe use of HDS [ 18 ], so it is pertinent for them to be equipped with adequate knowledge regarding HDS. Nonetheless, previous studies have reported that many pharmacists perceived their knowledge of HDS as inadequate, thus affecting their confidence in discussing these products with consumers or patients [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research in the US, Australia, Canada and Thailand, have been initiated to explore, define and review pharmacists' duty of care (if any) with respect to T&CM products. [24][25][26][27][28]. Despite the high level of integration of TCM that includes HMs, and modern medicine in China, few studies have explored this area in depth.…”
Section: Introductionmentioning
confidence: 99%